Elaboração de indicadores bibliométricos a partir de patentes de nanotecnologia - Peres, Lucas Salomão (Universidade Federal de São Carlos, 2012)
The need to assign values to consumer and globalization have created a new format in the economy. These phenomena have increased investments in technology until the crisis of 1970 that generated a reduction in economic growth and consequently reduction in research funding. This context created resources that could gauge the areas that lacked development. One of the solutions found was the creation of scientific and technological indicators. Nanotechnology is considered one of the key technologies of the century, has been conceptualized this way featuring how important application in multidisciplinary areas. The present study aims to indicate and analyze information on technological innovations in nanotechnology based on indicators developed from the full text of patents. To achieve the proposed objectives used data mining technique to generate knowledge based on information from U.S. patents. The results obtained so far have shown that North American patents grew 80.85% over the past five years, the main patent application is for semiconductor devices corresponding to 24.4% of all applications, Asian countries are distinguished by the large number of applications in semiconductor devices and fabrication and tract of nanostructures and among the patents deposited in the U.S. Brazil is the state that is 23° position in the ranking although it is still very distant from other countries examined in this research. For criteria of information extraction from textual structure of patent claims were created smaller structures than they could submit their own meanings and enable understanding lexical and logical. Using another filter extract the claims textual contain from Brazilians priority patents .
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Patentes; Indicadores de ciência e tecnologia; Nanotecnologia; Prospecção tecnológica; Patents; Indicators; Nanotechnology; Technological forecasting; CIENCIAS SOCIAIS APLICADAS